Chapter Public History e Public Pedagogy. Storia e pedagogia per lo sviluppo di una nuova «sfera pubblica» - TOGNON, Giuseppe (Studi e saggi, 2019)
The challenge of civil pedagogy - on which three examples are indicated in the final part of the article - is to go beyond the logics that guided it up to today to build a new patriotism that has the whole as a reference humanity. For centuries, civil pedagogy has been an integral part of the Nation building, but today it has to deal with the end of the age of Nations and with criticism of narratives based on historical-linguistic, religious, ethnic factors. The crisis of Welfare state is not only the result of its ability to produce well-being, but, first of all, it is an institutional crisis, especially in the school. Public History and Public Pedagogy are then called to retrace the history and the principles of modern institutions.